2021
DOI: 10.1186/s13102-021-00306-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-level red and near-infrared photobiomodulation on pain and function in tendinopathy: a systematic review and meta-analysis of randomized control trials

Abstract: Background Tendinopathy is a common clinical condition that can significantly affect a person’s physical function and quality of life. Despite exercise therapy being the mainstay of tendinopathy management, there are many potential adjunct therapies that remain under investigated, one of which is photobiomodulation (PBM). PBM uses varied wavelengths of light to create a biological effect. While PBM is used frequently in the management of tendinopathy, high quality evidence supporting its utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…Ghigiarelliet et al showed short-term effects of whole-body PBM in a sports population, without showing any conclusive change [19]. The effects of local PBM on pain are well known and established [39], and its usefulness has been shown in different conditions such as knee osteoarthritis [40], oral mucositis [41], idiopathic burning mouth syndrome [42], neck disability and chronic neck pain [43], pain and function in tendinopathy [44], myofascial temporomandibular disorder [45], fractures [46], central nervous diseases [47] and even in the microbiome [48]. On the other hand, other studies show that PBM does not decrease pain and disability, specifically in people with non-specific low back pain, although those studies analysed the use of local PBM and not whole-body PBM [49].…”
Section: Discussionmentioning
confidence: 99%
“…Ghigiarelliet et al showed short-term effects of whole-body PBM in a sports population, without showing any conclusive change [19]. The effects of local PBM on pain are well known and established [39], and its usefulness has been shown in different conditions such as knee osteoarthritis [40], oral mucositis [41], idiopathic burning mouth syndrome [42], neck disability and chronic neck pain [43], pain and function in tendinopathy [44], myofascial temporomandibular disorder [45], fractures [46], central nervous diseases [47] and even in the microbiome [48]. On the other hand, other studies show that PBM does not decrease pain and disability, specifically in people with non-specific low back pain, although those studies analysed the use of local PBM and not whole-body PBM [49].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study showing long-term results of whole-body PBM in a population suffering from FM, thus comparison with other studies is difficult. Studies showing the effects of PBM on different conditions have been published, as in oral mucositis ( MASCC/ISOO et al, 2020 ), central nervous diseases ( Yang et al, 2021 ), musculoskeletal conditions such as fractures ( Neto et al, 2020 ), knee osteoarthritis ( Vassão et al, 2021 ), neck disability and chronic neck pain ( Gross et al, 2013 ), pain and function in tendinopathy ( Tripodi et al, 2021 ) and myofascial temporomandibular disorder ( Sobral et al, 2021 ; Yang et al, 2021 ). Nevertheless, not all studies have found positive effects when using a PBM approach, as in Tomazoni et al (2020) , who found that local PBM did not improve pain and disability in patients suffering from non-specific low back pain, or Ghigiarelli et al (2020) who did not find significant improvement in a sport population when assessing performance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were no difference in the redox parameters and lysosomal hydrolases between the healthy and injured athletes at baseline prior to HILT, questioning the choices of outcomes in this study [ 88 ]. At present, there is a lack of high-quality evidence of the effect and underlying mechanism of photobiomodulation for the treatment of tendinopathy [ 89 ].…”
Section: Anti-oxidative Therapies For the Promotion Of Tendon Repairmentioning
confidence: 99%